Comparative data on left atrial appendage occlusion efficacy and clinical outcomes by age group in the Amplatzer™ Amulet™ Occluder Observational Study. Issue 2 (6th December 2020) - Freixa, Xavier; Schmidt, Boris; Mazzone, Patrizio; Berti, Sergio; Fischer, Sven; Lund, Juha; Montorfano, Matteo; Della Bella, Paolo; Lam, Simon Cheung Chi; Cruz-Gonzalez, Ignacio; Gage, Ryan; Omran, Heyder; et al.
Abstract: Aims: Left atrial appendage occlusion (LAAO) may be considered for patients with non-valvular atrial fibrillation (NVAF) and a relative/formal contraindication to anticoagulation. This study aimed to summarize the impact of aging on LAAO outcomes at short and long-term follow-up. Methods and results: We compared subjects aged <70, ≥70 and <80, and ≥80 years old in the prospective, multicentre Amplatzer™ Amulet™ Occluder Observational Study (Abbott, Plymouth, MN, USA). Serious adverse events (SAEs) were reported from implant through a 2-year post-LAAO visit and adjudicated by an independent clinical events committee. Overall, 1088 subjects were prospectively enrolled. There were 265 subjects (24.4%) <70 years old, 491 subjects (45.1%) ≥70 and <80 years old, and 332 subjects (30.5%) ≥80 years old, with the majority (≥80%) being contraindicated to anticoagulation. As expected, CHA2 DS2 -VASc and HAS-BLED Scores increased with age. Implant success was high (≥98.5%) across all groups, and the proportion of subjects with a procedure- or device-related SAE was similar between groups. At follow-up, the observed ischaemic stroke rate was not significantly different between groups, and corresponding risk reductions were 62, 56, and 85% when compared with predicted rates for subjects <70, ≥70 and <80, and ≥80 years old, respectively. Major bleeding and mortality rates increased with age, while the incidence of device-related thrombus tended to increase with age. Conclusions: Despite the increased risk for ischaemic stroke with increasing age in AF patients, LAAO reduced the risk for ischaemic stroke compared with the predicted rate across all age groups without differences in procedural SAEs. Graphical Abstract: